Bimbingan Belajar Berbasis Science Edutaiment Untuk Meningkatkan Minat Belajar Matematika Pada Masa Pandemi - Kiki Riska Ayu Kurniawati; Habib Ratu Perwira Negara; Farah Heniati Santosa; Habibi Ratu Perwira Negara (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2023)
Guaranteeing interest in learning so that it remains good during the pandemic is an important thing to do. The purpose of this research is to increase students' interest in learning mathematics using the science edutaiment method. The stages in carrying out activities are in the form of: Observation, interviews, identifying problems, finding solutions, outreach, and carrying out learning activities using the science edutaiment method. The results of the activity showed that students' interest in learning mathematics during the pandemic by providing tutoring using the science edutaiment method increased by 45% from the previous one.